1992
DOI: 10.1037/0021-9010.77.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Perceived equity, motivation, and final-offer arbitration in major league baseball.

Abstract: Final offer salary arbitration in major league baseball offers a unique institutional arrangement that creates a naturally occurring non-equivalent groups repeated measure research design. The structural arrangements allow for examination of anticipatory expectancy effects and for assessment of behavioral responses consistent with equity theory predictions. Additionally, equity theory can be tested without the methodological problems inherent in defining the referent other. Performance and mobility were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
1
31
0
2
Order By: Relevance
“…He found that where the players are experiencing underpayment and under conditions of the weaker future PRP link for batting averages and stronger link for home runs, batting average declined (consistent with equity predictions) and home runs did not (consistent with expectancy predictions). Bretz and Tomas (1992) also found that player performance increased in the season before salary arbitration in anticipation of increasing future salary. This supports the expectancy model predictions of increasing levels of performance when this is linked to attaining rewards.…”
Section: Prp In Professional Sportsmentioning
confidence: 90%
“…He found that where the players are experiencing underpayment and under conditions of the weaker future PRP link for batting averages and stronger link for home runs, batting average declined (consistent with equity predictions) and home runs did not (consistent with expectancy predictions). Bretz and Tomas (1992) also found that player performance increased in the season before salary arbitration in anticipation of increasing future salary. This supports the expectancy model predictions of increasing levels of performance when this is linked to attaining rewards.…”
Section: Prp In Professional Sportsmentioning
confidence: 90%
“…Outcomes are any consequences to the party of his participation in the relationship (Hunt et al 1983): they are ''conditions and goods that affect well-being, which includes psychological, physiological, economic, and social aspects'' (Kabanoff 1991, p. 417). Perceptions of equity or inequity result from a social comparison process, wherein a participant in an exchange relationship compares her inputs to and outcomes from the relationship with the inputs and outcomes of a 'comparison-other', who might be the other party in the relationship, specific others or general categories of others who are in similar exchange relationships, or her historical self (Bretz and Thomas 1992;Oldham et al 1986;Ronen 1986). The relationship participant will perceive the relationship to be equitable if and only if her outcome-to-input ratio (O/I ratio) is similar to the corresponding ratio of the comparison-other (Cosier and Dalton 1983).…”
Section: Stakeholder Responses To Inequity In the Firmstakeholder Relmentioning
confidence: 99%
“…As Keidel (, p. 608) stated, “The different varieties of team sports can serve as a living laboratory for organizational inquiry.” Sports‐based research also naturally lends itself to workforce analytics because of the availability of a multitude of performance data due to the frequency and regularity of events, transparency of changes in process and rules, and clarity of outcomes all combining to provide unique opportunities to observe, measure, and compare performance variables and relationships of interest over time as the data tends to be measured with great accuracy (Wolfe et al, ). More specifically, studies set in MLB have traditionally played an important role in the advancement of management theory over several decades in oft‐cited studies on topics, including labor market information asymmetries and investment (Blass, ); salary structure, equity, discrimination and arbitration (Bretz & Thomas, ; Hill & Spellman, ); managerial scapegoating (Gamson & Scotch, ); testing of equity versus expectancy theory (Harder, ); and many others. In terms of external validity, professional baseball teams have been favorably compared to broadcasting, advertising, accounting, law, bio research, public relations, consulting, and software development firms, in terms of having selection practices primarily based on credentials and expertise, development primarily based on on‐the‐job learning in an industry setting with tendencies toward high turnover and cross‐employer career paths (Sonnenfeld & Peiperl, , pp.…”
Section: Research Settingmentioning
confidence: 99%